Digital Extraction Column: Measurement and Modeling Techniques. Issue 7 (29th May 2020) - Hlawitschka, Mark W.; Schulz, Jonas; Wirz, Dominic; Schäfer, Jan; Keller, Alexander; Bart, Hans‐Jörg
Abstract: The digitization of extraction columns requires a profound knowledge of the present hydrodynamics/mass transport interaction as well as appropriate measurement techniques for the detection of relevant input and target values. In this article, the different techniques for droplet size distribution as well as concentration determination are presented and new methods for online evaluation are discussed. In combination with the simulation of droplet size, holdup and solute concentration distribution, an online‐capable process tool for controlling and optimizing extraction columns will be obtained. Abstract : Different measuring techniques for extraction columns for drop size and concentration determination are described and new methods for online evaluation are presented. In combination with the simulation, an online‐capable tool for process control of extraction columns is introduced.